Phenolic compounds from kenaf (Hibiscus cannabinus L.) seeds by ultrasound-assisted extraction - Wong, Yu Hua; Beh, Joo Sheng; Tan, Chin Ping; Long, Kamariah; Nyam, Kar Lin (Free Radicals and Antioxidants)
Introduction: There is great interest in the replacement of synthetic antioxidants with natural sources, especially from plant materials. Kenaf seed potentially contained phenolic compounds. Materials and Methods: Kenaf seed extract (KSE) was extracted by ultrasonic-assisted extraction. Then, the purification was carried out using silica gel column chromatography. Finally, the phenolic compounds were determined by high-performance liquid chromatography. Result: There were 11 phenolic acids identified from the purified KSE, which were identified as sinapic acid (3563.67 mg/100 g), ferulic acid (2085.55 mg/100 g), catechin hydrate (1189.02 mg/100 g), tannic acid (1032.24 mg/100 g), naringin (385.75 mg/100 g), 4-hydroxybenzoic acid (382.51 mg/100 g), gallic acid (380.18 mg/100 g), 4-hydroxybenzaldehyde (372.00 mg/100 g), protocatehuic acid (207.04 mg/100 g), syringic acid (189.13 mg/100 g), and cinnamic acid (85.51 mg/100 g). Conclusion: The KSE was found to exhibit an antioxidant capability, and it is potentially suitable to be used as an alternative source of antioxidants.
Keywords: Antioxidant; chromatography; kenaf; phenolic; purification